Reducing misinformation: The role of confirmation frames in fact-checking interventions - Natalia Aruguete; Flavia Batista; Ernesto Calvo; Matías Guizzo Altube; Carlos G. Scartascini; Tiago Ventura (Inter-American Development Bank (IDB), 2023)
Previous research has extensively investigated why users spread misinformation online, while less attention has been given to the motivations behind sharing fact-checks. This paper reports a four-country survey experiment assessing the influence o f c onfirmation and refutation frames on engagement with online fact-checks. Respondents randomly received semantically identical content, either affirming accurate information ("It is TRUE that p") or refuting misinformation ("It is FALSE that not p"). Despite semantic equivalence, confirmation frames elicit higher engagement rates than refutation frames. Additionally, confirmation frames reduce self-reported negative emotions related to polarization. These findings are crucial for designing policy interventions aiming to amplify fact-check exposure and reduce affective polarization, particularly in critical areas such as health-related misinformation and harmful speech.
Keywords: D83; D91; 330; Misinformation; Fact-checking; Social media